Is There a Difference in the Professional Competence of Geography Teachers and Nonformal ESD Educators? Results of an Empirical Study - Reinke, Verena (Journal of Geography Education, 2021)
In the world action program, the training of ESD multipliers is clearly declared in a field of action as a goal, because competent actors are required to integrate ESD into education. So far, however, little is known about the ESD-specific professional competence of geography teachers and non-formal actors, there is a lack of empirical evidence, which is necessary to be able to present the competence of ESD groups of actors. The differences in professional competence were measured using the example topic “climate change”. The article presents the difference in professional competence between geography teachers and non-formal actors and gives an outlook on possible causes and consequences for the future training of ESD actors.